Rapid Mass Loss in West Antarctica Revealed by Swarm Gravimetry in the Absence of GRACE - Zhang, Chaoyang (author); Shum, C. K. (author); Bezděk, Aleš (author); Bevis, Michael (author); De Teixeira Da Encarnação, J. (author); Tapley, Byron D. (author); Zhang, Yu (author); Su, Xiaoli (author); Shen, Qiang (author) (Geophysical Research Letters, 2021)
GRACE observations revealed that rapid mass loss in the West Antarctic Ice Sheet (WAIS) abruptly paused in 2015, followed by a much lower rate of mass loss ((Formula presented.) Gt yr −1 ) until the decommissioning of GRACE in 2017. The critical 1-year GRACE intermission data gap raises the question of whether the reduced mass loss rate persists. The Swarm gravimetry data, which have a lower resolution, show good agreement with GRACE/GRACE-FO observations during the overlapping period, i.e., high correlation (0.78) and consistent trend estimates. Swarm data efficiently bridge the GRACE/GRACE-FO data gap and reveal that WAIS has returned to the rapid mass loss state ((Formula presented.) Gt yr −1 ) that prevailed prior to 2015 during the GRACE intermission data gap. The changes in precipitation patterns, driven by the climate cycles, further explain and confirm the dramatic shifts in the WAIS mass loss regime implied by the Swarm observations. Astrodynamics & Space Missions